this book is not good for you - Bosch, Pseudonymous; Pseudonymous bosch (New York Boston Hachette Book Group Inc., 2009)
I promise, your taste buds will tingle. Your palate will sing! Oh no, have i accidentally tempted you to read this book? I will warn you, however, the most delicious things are never good for you... and this story is particularly scrumptious! In this tooth-rotting adventure, Cass's mom has been kidnapped by the sinister chocolatier Señor Hugo! Can Cass and Max-Ernest discover the evil ingredient before it's too late? If you're tempted, take a taste, but just remember... This book is not good for you.
Includes bibliographical references
English